An "on-off-super on" photoelectrochemical sensor based on quenching by Cu-induced surface exciton trapping and signal amplification of copper sulfide/porous carbon nitride heterojunction. (March 2021) - Liang, Dong; Luo, Junjun; Liang, Xiang; Wang, Haixia; Wang, Jianxiu; Qiu, Xiaoqing
Abstract: In this work, we report an "on-off-super on" photoelectrochemical sensor for probing hydrogen sulfide due to its toxicity in water environment by using porous carbon nitride as photoelectric transducers. Synthesized by an alkaline-assisted hydrothermal method, the porous carbon nitride photoanode exhibited a remarkable photocurrent on the initial "on" state. Cu 2+ immobilized on the surfaces of porous carbon nitride could significantly decrease the charge transfer efficiency and quench the photoelectrochemical signal in the "off" state. In addition, the introduction of S 2− ions could eliminate the influence of Cu-induced surface exciton trapping and amplify the photoelectrochemical signal due to the formation of carbon nitride/copper sulfide heterojunction, thus leading to the achievement of the ''super on'' state and subsequently detection of hydrogen sulfide. More importantly, this photoelectrochemical sensor shows the excellent performance for probing hydrogen sulfide in terms of stability, selectivity, sensitivity and fabrication cost. Enabled by a unique "on-off-super on" strategy, it could serve as a reference for developing the new class of photoelectrochemical sensor. Graphical abstract: Image 1 Highlights: An "on-off-super on" PEC sensor was proposed. Cu-induced surface exciton trapping is helpful to quench the PEC signal. The formation the p-n junction of CuS/p-CN achieves the "super on" PEC signal. This PEC sensor shows a broad detection range for detection of H2 S.